Professional Pitchers Display Differences in UCL Morphology and Elbow Gapping During Moving Valgus Stress Testing After UCL Reconstruction. Issue 11 (1st November 2021) - Kissenberth, Michael J.; Thigpen, Charles A.; Bailey, Lane Brooks; Campbell, Joel; Geist, Derik J.; Schweppe, Mark L.; Wyland, Douglas J.; Hawkins, Richard J.; Noonan, Thomas J.; Shanley, Ellen
Background: Ulnar collateral ligament (UCL) reconstruction (UCLR) of the elbow has received much attention given the rise in incidence among baseball pitchers. Stress ultrasonography has been demonstrated to be a critical evaluation tool of the UCL. No study has dynamically evaluated the ability of UCLR to restore normal kinematics. Purpose/Hypothesis: The purpose of this study was to compare ulnohumeral gapping during a moving valgus stress test as well as UCL thickness between professional pitchers with and without UCLR. We hypothesized that the ulnohumeral joint will display greater gapping and the UCL graft will be thicker in pitchers after UCLR compared with uninjured pitchers. Study Design: Cross-sectional study; Level of evidence, 3. Methods: Ultrasonography was used to measure the medial ulnohumeral joint distance and the UCL thickness of 70 asymptomatic professional baseball pitchers; 6 of the participants had a history of UCLR. Images were captured of the dominant (D) and nondominant (ND) elbows at the maximal cocking position under 2 loaded conditions within the moving valgus stress test arc: (1) gravity stress and (2) 2.5 kg (5.5 lb) of valgus force using a dynamometer. Intra- and interrater reliability of the measurements was established with intraclass correlation coefficients (ICCs). Separate mixed-model analyses of variance (D side × UCL) were used to compare the D and ND elbow variables between pitchers with and without a history of UCLR. Results: All measurements displayed good reliability according to ICCs. Pitchers with a history of UCLR demonstrated less gapping (5.6 ± 2.9 vs 4.2 ± 1.2 mm; P = .002) and greater UCL graft thickness (0.17 ± 0.07 vs 0.11 ± 0.08 mm; P = .03) compared with the native ligament in pitchers without prior UCL injury. Conclusion: Our data demonstrated that the UCLR results in a thicker, stiffer construct with less medial elbow gapping than the anatomical UCL. Using ultrasound to evaluate the UCL was a reliable, efficient, and clinically feasible method to assess UCL thickness and joint gapping in players with a history of UCLR. Future studies may consider this approach to evaluate surgical techniques and graft types for UCLR.